Implementasi Meningkatkan Minat Usaha Mahasiswa Melalui Usaha Puding Fla Susu: Implementation to Increase Students' Interest in Entrepreneurship through Milk Pudding Business - Simatupang, Evi Trisna; Salsabila, Gadis; Syahfitri, Nasha Astrid; Harefa, Meilinda Suriani (J-CoSE: Journal of Community Service & Empowerment, 2024)
The aim of this research is to develop students' business interest in selling milk flan pudding business. This business is a small business that can be pursued by students or other groups. This flan pudding business is very easy to make with affordable capital, the only problem with this business is that flan pudding cannot be stored for too long because the production period is only around 2-3 days, after that the pudding will be stale and smell bad. Fla pudding is liked by many people, especially young people, such as school children or students at a price of Rp. 5000 and is usually sold via social media such as WA and other platforms and can also be promoted directly to buyers. The price of this milk flan pudding can still be said to be affordable because at that price, buyers already get milk flan pudding in one large cup and with various flavors, there are chocolate, strawberry and grape flavors.